Knowledge, attitude, perception and belief of Guyanese health workers and the general population pertaining to tuberculosis - Persaud, Shamdeo (Ministry of Health [Georgetown]GY, 2008)
Assesses the knowledge, attitudes, perceptions and beliefs of all categories of health care workers and the public in all 10 regions of Guyana. Makes use of the 2007 Guyana TB KAPB survey to develop a base-line measurement.